Assessing structural integrity responses of coralline algae across the PETM - Leanne Melbourne; Daniela N Schmidt; Suman Sarkar (PANGAEA, 2025)
Coralline red algae are key benthic components of shallow-marine ecosystems, which globally support high levels of biodiversity. Modern short term experiments show negative responses of coralline algae to warming and higher CO2, in which a weakening of structural integrity is seen. However, short-term experiments do not account for acclimation and multi-generation exposure. The geological record allows for us to assess responses to long-term enivronmental change and account for acclimation and multi-generation exposure. We measured the cellular structure in species of two cosmopolitan genera, Sporolithon and Lithothamnion, from Meghalaya, NE India (Eastern Tethys), before and during the Palaeocene-Eocene Thermal Maximum (PETM, ~55.8 Ma), the most pronounced hyperthermal, a geologically abrupt environmental change in Earth history characterized by rapid ocean warming, acidification and sea level rise of the Cenozoic.